Are non-pregnant women afraid of childbirth? Prevalence and predictors of fear of childbirth in students - Lana Žigić Antić; Sandra Nakić Radoš; Nataša Jokić-Begić (Taylor & Francis Group, 2019)
Introduction: Fear of childbirth (FOC) has been mostly studied in peripartum women; however, it can be present in non-pregnant young women, and the question is whether it occurs even before pregnancy planning. Objective: (1) to determine the prevalence of clinically significant FOC in non-pregnant female students, and (2) to investigate the role of anxiety sensitivity (AS), trait anxiety, childbirth pain expectancy, and sources of birth knowledge for FOC. Methods: Non-pregnant female students (N = 374) from different study programmes (health studies, social sciences and humanities, and biotechnical studies) participated in the study. They completed Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ, version A), The State-Trait Anxiety Inventory (STAI-T), Anxiety Sensitivity Index (ASI), the average expected labor pain, and sources of information about childbirth. Results: The results showed that 25.9% of students reported clinically significant FOC. FOC could be predicted by postponing pregnancy planning, the high expectancy of labor pain, high trait anxiety, and high physical dimension of AS. Students from health sciences reported a lower level of FOC, as opposed to social science and humanities' students. Students reported receiving the most information about childbirth from family and the least from the professional books. Conclusions: Fear of childbirth is highly prevalent in the sample of young nulliparous women with one in four women reporting clinically significant fear. The higher levels of the FOC could be predicted, by AS, trait anxiety, expected labor pain, and sources of knowledge about the childbirth. Implications of the findings are discussed.